Even broken clocks are right twice a day: The utility of models in the clinical reasoning process. - Rodriguez AD; Rothi LJG (Advances in Speech Language Pathology, 2006)
The use of cognitive neuropsychological models in rehabilitation has been widely debated among professionals in a variety of disciplines. Some believe that models can be used to develop 'model-based' treatment, while others maintain that the role of models in rehabilitation is more limited in scope. Despite the debate, it is widely accepted that models do contribute to the rehabilitation process. While models can assist in clinical decision making, it is important to understand the underlying assumptions of the model and be aware that the 'truth' of a model is something we seek and rarely achieve, and this evolution remains a continuing process. This article compares the Praxis Model of Rothi and Heilman (1997) and the Sketch Model of de Ruiter (1998), highlighting the contrasting underlying assumptions regarding the relationship of gesture and language. The limitations of these models is then used as segue for the discussion of the current debate regarding cognitive neuropsychological models and rehabilitation. We conclude with our view that models are assistive rather than directive.